Translation of Indirect Speech Acts - Gladush, Nadia F. (Синопсис: текст, контекст, медіа, 2013)
The article elucidates translation techniques in reproducing English Indirect Speech Acts into Ukrainian within the framework of pragmatics. A special attention is given to indirect directives. In conclusions, an attempt is made to analyze these techniques and their relevance for teaching English